Research on the Influence of Media Attention on Annual Stock Returns - Ren, Yuezhuo (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of information technology, media attention not only affects investors' information acquisition and cognition, but also further affects stock returns by changing market sentiment and corporate governance mechanisms. This paper explores the influence of media attention on the annual stock returns of enterprises and tests the robustness of enterprises’ samples with different regions and equity properties, which increases the richness of relevant literature and provides a useful reference for investors, regulators and media, so as to better understand the influence of media attention on the stock market and its potential effects.